Peripheral Ulcerative Keratitis: A Review - Kiana Hassanpour; Reem H. ElSheikh; Amir Arabi; Charles R. Frank; Abdelrahman M. Elhusseiny; Taher K. Eleiwa; Shiva Arami; Ali R. Djalilian; Ahmad Kheirkhah (Journal of Ophthalmic & Vision Research, 2022)
Abstract Peripheral ulcerative keratitis (PUK) is a rare but serious ocular condition that is an important clinical entity due to its ophthalmological and systemic implications. It is characterized by progressive peripheral corneal stromal thinning with an associated epithelial defect and can be associated with an underlying local or systemic pro-inflammatory condition, or present in an idiopathic form (Mooren ulcer). Associated conditions include autoimmune diseases, systemic and ocular infections, dermatologic diseases, and ocular surgery. Cell-mediated and auto-antibody-mediated immune responses have been implicated in the pathogenesis of PUK, destroying peripheral corneal tissue via matrix metalloproteinases. Clinically, patients with PUK present with painful vision loss, a peripheral corneal ulcer, and often adjacent scleritis, episcleritis, iritis, or conjunctivitis. Diagnostic evaluation should be focused on identifying the underlying etiology and ruling out conditions that may mimic PUK, including marginal keratitis and Terrien marginal degeneration. Treatment should be focused on reducing local disease burden with topical lubrication, while simultaneously addressing the underlying cause with antimicrobials or anti-inflammatory when appropriate. Existing and emerging biologic immunomodulatory therapies have proven useful in PUK due to autoimmune conditions. Surgical treatment is generally reserved for cases of severe thinning or corneal perforation.